Implications of the European integration: revisiting the hypothesis of 'hub-and-spokes' model - Tinatin Akhvlediani; Katarzyna Sledziewska (Baltic Journal of Economics, 2017)
Already in 1994, Baldwin predicted the formation of the 'hub-and-spokes' model to describe the outcomes of economic integration across the European Union (EU) implying marginalization of the new EU member states. We examine the validity of this hypothesis by putting an emphasis on Visegrad group of countries (The Visegrad four (V-4): Poland, the Czech Republic, Slovakia and Hungary) and investigate the impact of the European integration scheme on their export performances. To conduct the analysis, we estimate the augmented gravity model for the panel data of the exports of V-4 with the rest of the world by employing pseudo-Poisson maximum likelihood estimator. Estimation results do not favour the creation of the 'hub-and-spokes' model, but rather demonstrate that integration within the EU was quite beneficial for V-4 without giving the origin neither to their peripherization nor to the loss of markets of the natural trade partners.
Keywords: 330; European integration; international trade; regionalism; gravity model; Visegrad group